Hubungan Antara Dukungan Sosial Dengan Penerimaan Diri Pada Pasien Diabetes Mellitus Tipe II - Noor Laila, Rahma, Setia Asyanti S.Psi, M.Si (2016)
Self acceptance is the ability of individuals to will love and receive themselves related to want and excess, and the positiveness in ourselves, see positive on life that is been spent and mengaktualisasikan potentials these individuals. Self acceptance influenced by several factors, one of the social support. Research aims to understand between a social influence of self acceptance in patients diabetes mellitus type II. Hypothesis advanced by in this research is a positive relations between a social self acceptance in patients diabetes mellitus type II. The study is done in Ulin district general hospital in Banjarmasin. The subject of study the research is 60 patients diabetes mellitus type II in clinics feet retinopathy and treatment of injuries. The sample collection done to technique quota of sampling and use the criteria inclusion and ekslusi. As for criteria inclusion in research is to patients diabetes mellitus type II, adults madya, outpatients, have a family, willing to become the subject of study. Criteria ekslusi to research this is the subject with complications heavy. A method of the data with a measuring instrument of scale social support and scale of self acceptance. While technique analysis the data used was correlation product moment of pearson. Based on the result is collected (a) there is a positive relationship very significant between support social self acceptance, (b) outcomes this research show support social are being, (c) from the result of this research also self acceptance are being. (d) a contribution effective social support to self acceptance of 49,28 %. These findings it implies the importance of social support of self acceptance in patients diabetes mellitus type II. The result will be discussed further. Keywords : Social support, Self acceptance, Diabetes mellitus